Brainstem microglial cell morphology in neonatal rats with necrotizing enterocolitis and the effects of prenatal heparin-binding epidermal growth factor-like growth factor - Andrei Radulescu; Christopher G Wilson; Vonita Chawla; Yomara S Mendez; Lorraine C Siebold; Julia C Vickery; Marla A Sacks; Georgi D Mladenov (World Journal of Pediatric Surgery)
Background Necrotizing enterocolitis (NEC) is associated with increased neurodevelopmental impairment. Gut-brain interactions through the brainstem may be central to NEC-related microglia-driven neuroinflammation. Heparin-binding epidermal growth factor-like growth factor (HB-EGF) has intestinal protective properties and is a potential therapy for NEC. The aim of this study is to test the hypothesis that HB-EGF in pregnant rats reduces both NEC incidence and proinflammatory changes in the brainstem microglia of newborn rats.Methods We compared four experimental groups, HB-EGF+/NEC–, HB-EGF–/NEC–, HB-EGF+/NEC+ and HB-EGF–/NEC+, depending on whether HB-EGF was given prenatally, and whether the newborn rats underwent the NEC induction protocol. We stained brainstem microglia and performed fractal analyses to provide objective measures of morphological changes.Results NEC incidence was lower in the HB-EGF+/NEC+ group (n=64, p<0.005) than in the HB-EGF–/NEC+ group. Brainstem microglia of breastfed rats had a larger cell area, perimeter, roughness, and less circularity compared with smaller, denser, compact cells in the NEC+ pups (p<0.0001, n=320 cells). HB-EGF+/NEC+ and HB-EGF–/NEC+ pups had similar-appearing microglia.Conclusions Prenatal HB-EGF treatment reduces NEC incidence in neonatal rats. NEC-related proinflammatory changes are seen in microglial cells present in crucial centers controlling the gut-brain pathway. HB-EGF has a growth-promoting effect on healthy microglia in the offspring but does not avert microglial activation in the brainstem of newborn rats with NEC.